1997
DOI: 10.1046/j.1365-2141.1997.1772993.x
|View full text |Cite
|
Sign up to set email alerts
|

Bernard‐Soulier syndrome Karlstad: Trp 498→Stop mutation resulting in a truncated glycoprotein Ibα that contains part of the transmembranous domain

Abstract: Summary. In Bernard-Soulier syndrome, a hereditary bleeding disorder, the platelets are deficient in the glycoprotein (GP) Ib-IX-V complex, a major receptor for the von Willebrand factor. The components of the complex are encoded by separate genes. Patients with this syndrome have a variable expression level of the receptor protein on platelets depending on the specific genetic abnormality. We describe a patient with life-long bleeding symptoms, who is homozygous for a unique stop mutation, Trp 498 → Stop in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…The GPIba fragment was also not detected in the patient's plasma. To investigate whether different mutation types correlate with patterns of protein expression, we collected data from the previously reported patients harboring a homozygous GPIba mutation causing a premature stop codon (Table 2) [4,5,[9][10][11][12][13][14][15][16]. The GPIba protein expression profile in the present case was similar to that reported by Kanaji et al [12], who demonstrated a homozygous frameshift mutation in the GPIba gene, resulting in 294 amino acids followed by 40 altered amino acids.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The GPIba fragment was also not detected in the patient's plasma. To investigate whether different mutation types correlate with patterns of protein expression, we collected data from the previously reported patients harboring a homozygous GPIba mutation causing a premature stop codon (Table 2) [4,5,[9][10][11][12][13][14][15][16]. The GPIba protein expression profile in the present case was similar to that reported by Kanaji et al [12], who demonstrated a homozygous frameshift mutation in the GPIba gene, resulting in 294 amino acids followed by 40 altered amino acids.…”
Section: Discussionsupporting
confidence: 79%
“…The GPIba protein expression profile in the present case was similar to that reported by Kanaji et al [12], who demonstrated a homozygous frameshift mutation in the GPIba gene, resulting in 294 amino acids followed by 40 altered amino acids. On the contrary, BSS patients with a homozygous nonsense mutation (S444X or W498X) in GPIba had a truncated protein in the cytoplasm of the platelets and the plasma [5,9]. These observations may suggest that the mutated Immunoblot analysis of platelets.…”
Section: Discussionmentioning
confidence: 97%
“…In the first, which encompasses the large majority of patients, GPIba is present only in residual amounts, and the other components of the GPIb-IX-V complex are affected to a varying degree (from normal to residual amounts) (Kanaji et al, 1997;Wright et al, 1993;Ware et al, 1990Ware et al, , 1993Simsek et al, 1994a, b;Li et al, 1995a, b;Kunishima et al, 1994;De La Salle et al, 1995a;Margaglione et al, 1995;Yamamoto et al, 1995;Holmberg et al, 1997;Kenny et al, 1997; Afshar-Kargan & Lopez, (Table I). The results expected for a normal gene and a gene with the T1811C substitution are shown.…”
Section: Discussionmentioning
confidence: 99%
“…Defects in any of the genes encoding GP Iba, GP Ibp and GP IX may cause absence or dysfunction of the protein complex on the platelet surface and so result in BSS; thus, it appears probable that the proper expression of the GP Ib/IX/V complex requires all these subunits (14). Most of the BSS mutations occur in the GP Iba gene (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29), but mutations have also been found in the GP IX and GP IbP genes (24,(30)(31)(32)(33)(34)(35)(36)(37). No mutation leading to BSS has been reported in the GP V gene.…”
mentioning
confidence: 99%